2021
DOI: 10.3390/vaccines9020123
|View full text |Cite
|
Sign up to set email alerts
|

Influenza and Pneumococcal Vaccination in Non-Infected Cardiometabolic Patients from the Americas during the COVID-19 Pandemic. A Sub-Analysis of the CorCOVID-LATAM Study

Abstract: Background: Influenza vaccination (IV) and Pneumococcus vaccination (PV) are recommended for patients with cardiometabolic diseases. This study aimed to evaluate the immunization rate of ambulatory cardiometabolic patients during the COVID-19 pandemic in the Americas. Methods: Electronic surveys were collected from 13 Spanish speaking countries between 15 June and 15 July 2020. Results: 4216 patients were analyzed. Mean age 60 (±15) years and 49% females. Global IV rate was 46.5% and PV 24.6%. Vaccinated patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…found an influenza vaccination percentage of 51.6 % and a pneumococcal vaccination of 16.2 % in the general population in Argentina before the pandemic [6] . In line with the aforementioned, the Cor-COVID LATAM survey found in the Southern Cone an influenza percentage of 69 % and pneumococcal percentage of 43 % at the beginning of the COVID pandemic [9] . These percentages are similar to those we found in our high-risk population, but are far from ideal.…”
Section: Discussionsupporting
confidence: 74%
“…found an influenza vaccination percentage of 51.6 % and a pneumococcal vaccination of 16.2 % in the general population in Argentina before the pandemic [6] . In line with the aforementioned, the Cor-COVID LATAM survey found in the Southern Cone an influenza percentage of 69 % and pneumococcal percentage of 43 % at the beginning of the COVID pandemic [9] . These percentages are similar to those we found in our high-risk population, but are far from ideal.…”
Section: Discussionsupporting
confidence: 74%
“…Among the countries of the Americas, confidence in vaccination by patients is unevenly distributed. Recent data from the CorCOVID-LATAM study, conducted in 13 Latin American countries, has reported differences in the vaccination rate according to economic income and educational level [ 187 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the CorCOVID LATAM study recently published by IASC demonstrated that there are profound regional differences in vaccination rates [ 187 ]: they were very low in the tropical countries of the Americas compared to the countries of the Southern Cone (approximately 50% less), which may partly reflect medical lack of knowledge regarding the circulation of influenza and seasonal peaks even in tropical countries. Of note, that study also found differences in vaccination rates in relation to economic strata and the educational level of the patients.…”
Section: Resultsmentioning
confidence: 99%
“…These results have been discussed extensively in a separate publication because a comprehensive detail of the findings is deserved. Some differences can be accounted by the fact that some of the centers that participated in the study, belonged to centers of reference in geographic areas with high population density 17 .…”
Section: Discussionmentioning
confidence: 99%